Object disorientation - Wyrich, Marvin; Hofmeister, Johannes; Apel, Sven; Siegmund, Janet (IEEE software, 2025)
Our study aims to uncover the essence of object-oriented programming - its fundamental ideas, concepts, and principles - through a scoping review of prominent views in both academic publications and nonacademic sources, such as industry reports or practitioner blogs.